2017
DOI: 10.1002/jcb.27143
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Platelet‐derived growth factor subunit B is required for tendon‐bone healing using bone marrow–derived mesenchymal stem cells after rotator cuff repair in rats

Abstract: As a common cause of shoulder pain and disability, rotator cuff injury (RCI) represents a debilitating condition affecting an individual's quality of life. Although surgical repair has been shown to be somewhat effective, many patients may still suffer from reduced shoulder function. The aim of the current study was to identify a more effective mode of RCI treatment by investigating the effect of platelet-derived growth factor subunit B (PDGF-B) on tendon-bone healing after RCI repair by modifying bone marrow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Animal experiments were performed according to the Rules and Regulations of the Animal Care and Use Committee at our University. BMSCs were isolated from rat bone marrow as described previously [10]. Briefly, bone marrow was flushed from the bone marrow cavities, collected into centrifuge tubes, and mononuclear cells were isolated by Ficoll density gradient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiments were performed according to the Rules and Regulations of the Animal Care and Use Committee at our University. BMSCs were isolated from rat bone marrow as described previously [10]. Briefly, bone marrow was flushed from the bone marrow cavities, collected into centrifuge tubes, and mononuclear cells were isolated by Ficoll density gradient.…”
Section: Methodsmentioning
confidence: 99%
“…Recent findings show that adipose tissue-derived mesenchymal stromal cells and tendon stem/progenitor cells (TSCs) can modulate the inflammatory environment by regulating the activities of resident macrophages to enhance tendon healing [8, 9]. Indeed, one study showed that bone marrow-derived multipotent mesenchymal stromal cells (BMSCs) can improve early tendon healing both histologically and biomechanically [10]. However, the implantation of BMSCs can also result in ectopic bone formation in the tendon or contribute to teratoma formation [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown to promote tendon-to-bone healing by up-regulating TGF-β expression in BMSCs after ACL reconstruction by adjusting the signal pathway TGF-β/MAPK. The effect of platelet-derived growth factor subunit B (PDGF-B) on tendon-bone healing after rotator cuff injury repair by modifying BMSCs was then investigated by Wang et al [ 80 ]. BMSCs were transfected with recombinant lentiviral vector-encoded PDGF-B shRNA, overexpressed Pc-DNA PDGF-B, and irrelevant plasmid.…”
Section: Bmscsmentioning
confidence: 99%
“…In recent years, researchers have used a variety of biological techniques to promote the regeneration of fibrocartilage, attempting to restore the tissue morphology and composition of the normal tendon graft-bone interface. There are currently four major treatment methods: mechanical stress stimulation [8], cell growth factor therapy [9,10], mesenchymal stem cell therapy [11], and biomaterial enhancement [12]. Although most of the results from these methods reported cartilage regeneration and improved tensile strength, the mechanical properties were not fully restored, and some methods have not been approved for clinical application.…”
Section: Introductionmentioning
confidence: 99%